Some information security problems of cloud data storage - Oleg Y. Madatov (Безопасность информационных технологий, 2018)
Last years the systems of remote data storage based on the Cloud Storage technologies have become widely used. This popularity is explained by its significant advantages for the users as compared to any other technologies of storing and accessing data. Indeed, a remote access of information located in the cloud storage with the help of computers, smartphones, tablets and other similar devices provides an opportunity for its owner to use the data needed at any time and practically everywhere (via the Internet).